Sebo bovino e emulsificante na dieta de suínos em crescimento e terminação - Santos, Kássia Moreira (2014)
This study aimed to determine the chemical and metabolizable energy of beef tallow and evaluate this feedstuff as an alternative lipid source in diets for growing and finishing pigs with or without emulsifier addition, on performance, digestibility of the nutrients, serum triacylglycerols, carcass characteristics and economic evaluation. For the metabolism assay a total of 15 barrows were used with an initial weight of 22.03 ± 0.62 kg and distributed in a completely randomized design, using the total of feces and urine method. The treatments were: RR - basal diet, formulated based on corn and soybean meal; RT1 - ration test comprised 95% of basal diet and 5% beef tallow and RT2 - test diet composed of 90% of basal diet and 10% beef tallow. The beef tallow showed 99.94% of dry matter and 7130.97 kcal of metabolizable energy (ME)/kg. To test the performance, a total of 30 barrows with an initial weight of 24.85 ± 1.18 kg were distributed in a randomized block design with five treatments and six repetitions of an animal. The treatments differed in fat source included, level of ME and addition of emulsifier, as much: T1 - diet with soybean oil and 3230 kcal ME/kg; T2 - diet with beef tallow and 3230 kcal ME/kg; T3 - diet with beef tallow and 3080 kcal ME/kg; T4 - diet with beef tallow, 3080 kcal ME/kg and addition of 0.1% of emulsifier; T5 - diet with beef tallow, 2930 kcal ME/kg and addition of 0.1% of emulsifier. It was not observed effects on variables of feed intake and average daily gain in all phases. However, it was observed that there was a significant difference in feed conversion in growing II and finishing phase; animals fed the diet containing beef tallow and reduction in energy to 3080 kcal ME/kg (T3) and 2930 kcal ME/kg with emulsifier (T5) presented worse feed conversion. There was no significant difference (P>0.05) among levels of triglycerides in the blood and carcass characteristics (weight, yield and carcass length, amount and percentage of lean meat, backfat thickness, loin depth and fat depth, loin eye area and fat area and meat/fat ratio). Depending on the energy level, beef tallow can replace soybean oil as a lipid source in diets for pigs during the growing and finishing phases. The reduction of metabolizable energy at 150 kcal/kg with the use of beef tallow can to be compensated with the addition of emulsifier.